Terminalia catappa fruit and its industrial application: A review - M.H.A. Jahurul; S. Islam; Norazlina Mohammad Ridhwan; A. Shihabul; K.L. Nyam; I.S.M. Zaidul (Elsevier B.V., 2025)
Some underexploited fruit species can be used for the extraction and isolation of functional/bioactive compounds, playing an important role in maintaining human health. T. catappa leaves and fruits have many medicinal uses, including antioxidant, anti-inflammatory, anticancer, antidiabetic, leprosy and headaches. The aim of this review is to describe the composition of T. catappa kernels which are examined from a critical interpretation concerning the suitable use. This review also compares the oil yields and their physicochemical properties for the purpose of evaluating the potential of T. catappa kernels as a source of natural edible oil with potential industrial uses. The demand for healthier vegetable oils is growing by the day as the primary sources of saturated oils are from animals and unsaturated oils from plants. Different parts of T. catappa, such as fruit flesh, seed, and bark are highly nutritious and rich in bioactive compounds. T. catappa kernel is usually consumed raw or roasted and has an almond-like taste because of its high unsaturated oil content (43.36–63.65 %). Highly unsaturated T. catappa kernel oil (TCKO) indicated that it can easily oxidize and be chemically unstable. Thus, it is not suitable to be used in its present state as an industrial fluid. T. catappa kernels could be a useful new source of edible oils that could also allow economic exploitation.